Customer Experience sebagai Faktor Pendorong Repeat Visit Intention pada Industri Kreatif Photobox: Studi Kualitatif pada Urarchive Studio Mall Banjarmasin - Lola Salma; Anjel Leoni Putri Ramadhani (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the role of customer experience as a driving factor of repeat visit intention in the creative photobox industry at Urarchive Studio Mall Banjarmasin. This research employed a qualitative approach with a descriptive method through in-depth interviews with the management of Urarchive Studio. The findings indicate that customer experience plays an important role in increasing customers’ intention to revisit. Customer experience is created through unique thematic concepts, high-quality facilities, responsive services, and innovations that follow current trends. In addition, enjoyable experiences also encourage customer loyalty and positive word of mouth. The study concludes that effective management of customer experience can become an important strategy in maintaining competitiveness and business sustainability in the creative photobox industry.